Resolving responsibility gaps for lethal autonomous weapon systems - Smith, Patrick Taylor (Frontiers in Big Data, 2022)
This paper offers a novel understanding of collective responsibility for AI outcomes that can help resolve the “problem of many hands” and “responsibility gaps” when it comes to AI failure, especially in the context of lethal autonomous weapon systems.